Climate Variations and Implementation of Climate Planning in The Municipalities of Zio1 (Togo) And Zou (Benin) - Houndjo, Komlan; Kpotchou, Koffi; Nimon, Pouwereou (Journal of Ecohumanism, 2025)
Climate variations negatively impact municipalities in West Africa. In the municipalities of Zio1 and Zou, climate variations have consequences on the local economy. However, these municipalities are unable to implement climate actions defined at the local level. This research is based on the following hypothesis : in Zio1 as in Zou, the same difficulties in implementing climate planning are explained by choices of carrying out socio-economic development projects to the detriment of implementing climate actions. This article aims to examine the explanatory factors for the difficulties in implementing climate planning in the municipalities of Zio1 and Zou. In this research, climate variables from gridded observed data for the years 1981 to 2022 were used to analyze current climate conditions. For the analysis of future climate conditions, namely from 2021 to 2050, nine general circulation models were used. For socio-demographic data, a survey was conducted among 449 people aged 18 and over, spread across the territories of Zio1 and Zou. The results show that the implementation of climate actions is not a priority in the municipalities of Zoi1 and Zou. Several projects carried out at the local level are not sized to take into account climate variations.